Comparative Analyses of Mitochondrial Genomes Provide Evolutionary Insights Into Nematode-Trapping Fungi - Zhang, Ying; Yang, Guangzhu; Fang, Meiling; Deng, Chu; Zhang, Ke-Qin; Yu, Zefen; Xu, Jianping (Frontiers in Microbiology, 2020)
Predatory fungi in Orbiliaceae (Ascomycota) have evolved a diversity of trapping devices that enable them to trap and kill nematodes, other small animals, and protozoans. These trapping devices include adhesive hyphae, adhesive knobs, adhesive networks, constricting rings, and non-constricting rings. Their diversity and practical importance have attracted significant attention from biologists, making them excellent model organisms for studying adaptative evolution and as biological control agents against parasitic nematodes. The putative origins and evolutionary relationships among these carnivorous fungi have been investigated using nuclear protein-encoding genes, but their patterns of mitogenome relationships and divergences remain unknown. Here we analyze and compare the mitogenomes of 12 fungal strains belonging to eight species, including six species representing all four types of nematode trapping devices and two from related but non-predatory fungi. All 12 analyzed mitogenomes were of circular DNA molecules, with lengths ranging from 146,101 bp to 280,699 bp. Gene synteny analysis revealed several gene rearrangements and intron transfers among the mitogenomes. In addition, the number of protein coding genes (PCGs), GC content, AT skew, and GC skew varied among these mitogenomes. The increased number and total size of introns were the main contributors to the length differences among the mitogenomes. Phylogenetic analyses of the protein-coding genes indicated that mitochondrial and nuclear genomes evolved at different rates, and signals of positive selection were found in several genes involved in energy metabolism. Our study provides novel insights into the evolution of nematode-trapping fungi and shall facilitate further investigations of this ecologically and agriculturally important group of fungi.